How did Swiss small and medium enterprises weather the COVID-19 pandemic? Evidence from survey data - Christina Nicolas; Nathalie Brender; David Maradan (Journal of Risk and Financial Management, 2023)
The COVID-19 pandemic had unprecedented consequences on businesses and, in particular, small and medium enterprises (SMEs). The aim of this paper is to empirically study the impact of the COVID-19 sanitary crisis on Swiss SMEs two years after the onset of the pandemic. Using a sample of 149 SMEs operating in the French-speaking region of Switzerland, we find that revenue loss across the full sample averaged 14% in 2020 compared to 2019. Our findings show that firm characteristics are not significant in explaining turnover loss while business management strategies such as business restructuring, remote working, and prioritizing employee protection were significantly associated with revenue. Our results suggest that remote work should be gradually introduced in sectors of activity whenever possible to reduce the financial burden of any future pandemic on SMEs. Additionally, we quantify the impact of closure on SMEs and find that firms having reported to have closed partially or completely due to sanitary restrictions were impacted seven times more in terms of revenue loss compared to SMEs that did not cease their activity during the COVID-19 crisis. This paper contributes to our understanding of the magnitude of the financial impact of the COVID-19 pandemic on SMEs and highlights the importance of SMEs adopting efficient business management strategies, and implementing measures to support smaller firms by public authorities in times of crisis.
Keywords: M1; M2; G3; G4; 650; COVID-19; crisis management; financial management; firm performance; small and medium enterprises; SME